Osiadanie Półprzestrzeni Konsolidującej pod Działaniem Obciążenia Skupionego - Sobczyńska, Z. (Engineering Transactions, 1966)
The subject of the present considerations is a semi-infinite consolidating body loaded by a concentrated force acting on its surface. The considerations are based on the theory of liquid flow through porous deformable bodies established by Biot. As a result of solution of a set of equations the linear consolidation theory, an equation is obtained enabling us to determine the relative subsidence of the surface of the semi-infinite body in function of time. The solution can be used as a Green’s function for the construction of the solution for any time-variable load acting on the boundary, In conclusion are given graphs illustrating the relative subsidence of the surface for sandstone at the time t = 1 sec, t = 1 h and t → ∞. The latter graph coincides with the solution of the Flamant problem known from the theory of elasticity. It is shown also that there is no subsidence at t = 0, which seems to suggest that the notion of "instantaneous" subsidence at t = 0, introduced by FLORIN and BIOT is not correct.